Membangun kesadaran investasi pasar modal syariah mahasiswa UIN Salatiga - Sriani, Endang; Zami, Muhammad Taufiq Zam (Penamas: Journal of Community Service, 2024)
Investment is an essential instrument for the stability of capital markets and the economic growth of a country. Therefore, increasing awareness among younger generations about capital market investments is crucial, as it can help them manage finances and navigate future economic challenges. The objective of the educational and mentoring program for students of the Faculty of Sharia at UIN Salatiga regarding investment in the Sharia capital market is to enhance inclusive financial literacy and foster a community of young people who are aware of Sharia investments from an early age. Sharia investment education is particularly important for young generations to prevent them from falling into fraudulent investment schemes that could harm society. This program employs the Participatory Action Research (PAR) method, which involves five stages: developing an integrated system, analyzing the current situation, implementing developmental changes, evaluating or reviewing the outcomes, and generating reports and recommendations. The outcomes of this initiative include the realization of investment-literate students at the Faculty of Sharia UIN Salatiga, their understanding of Sharia capital market investment literacy, the practice of Sharia capital market investments, and the establishment of agents of change who are capable of educating the public about Sharia capital market investments, all of whom are part of the Sharia Stock Community of Salatiga.